Epistemologi Ḥadīth Kontemporer Muḥammad Shaḥrūr - Nasrulloh Nasrulloh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
The development of ḥadīth in Indonesia needs an epistemological change, from ideological to critical reasoning. If the epistemology does not change, the development of hadith will be stagnant. Ḥadīth studies will only repeat the views of scholars from the classical period that cannot be applied in Indonesian context, or even will not be able to contribute to solve socio-religious problems in modern society. It is because the development of method in understanding hadith is not only influenced by time and situation, but also by changes in epistemology. A contemporary thinker, Muḥammad Shaḥrūr has a controversial theory of hadith understanding where he uses burhÄnÄ« epistemology, an epistemology that prioritizes reason rather than text or intuition. The implication of Shaḥrūr's thought in the domain of contemporary ḥadīth studies will imply that hadith studies will take into account historical factors and social sciences to grasp meaning relevant and compatible with the principle of humanism. This is of course relevant with the principle of Islam, ṣāliḥ kull zamān wa makān.